Horse therapy benefits in children with cerebral palsy: integrative review (Research, Society and Development, 2021)
To analyze, in the scientific literature, the benefits of hippotherapy in children with cerebral palsy. Method: This is an integrative literature review, searching the SciELO, LILACS and PubMed databases. In health sciences (DeCS) were used: horse-assisted therapy, cerebral palsy, child, in Portuguese, English and Spanish. Complete articles from 2005 to 2020 were selected. The sample consisted of 11 complete articles, organized and characterized according to author, title, year, country of study, design and benefits of therapy. Equine therapy enables the significant improvement of motor function, as well as quality of life, by promoting self-care, improvement in self-esteem, and social interaction. The study offers important contributions to professionals from various areas of knowledge regarding the benefits of hippotherapy in the biopsychosocial development of children with cerebral palsy.